Renal functional outcomes in patients undergoing percutaneous cryoablation or partial nephrectomy for a solitary renal mass. (19th June 2017) - Mason, Ross J.; Atwell, Thomas D.; Lohse, Christine; Bhindi, Bimal; Weisbrod, Adam; Boorjian, Stephen A.; Leibovich, Bradley C.; Schmit, Grant D.; Thompson, R. Houston
Abstract : Objectives: To compare renal functional changes after percutaneous cryoablation (PCA) or partial nephrectomy (PN). Patients and Methods: Patients who underwent PCA or PN for a solitary renal mass at a single institution were identified (2003–2013). Estimated glomerular filtration rates (eGFRs) were calculated at baseline, discharge, and at the 3‐month follow‐up using the Chronic Kidney Disease Epidemiology Collaboration equation. Changes in renal function were compared between groups using 1:1 propensity score (PS) matching, adjustment for PS quintile, and inverse probability weighting (IPW). Results: There were 2 040 procedures available for the PS analyses, including 448 PCA and 1 592 PN. After PS adjustments, there were no significant differences in baseline clinical features between PCA and PN patients. In the PS‐matched analysis, the change in eGFR from baseline to discharge for PCA and PN patients was −3.1 and −1.1 mL/min/1.73 m 2, respectively ( P = 0.038), with percentage changes of −4.5% and 0% respectively ( P = 0.006). From baseline to the 3‐month follow‐up, the absolute change in eGFR for PCA and PN patients was −4.3 and −2.1 mL/min/1.73 m 2, respectively ( P = 0.008), and the percentage change was −6.1% and −2.4% respectively ( P = 0.005). Similar results were obtained after adjusting for PS quintiles and in the IPW analysis. Importantly, the rate of chronic kidney disease stage progression at the 3‐month follow‐up was similar between the groups (21% vs 18%). Conclusions: Our results confirm that both PCA and PN have a minor impact on renal function. While we observed a statistically greater decline in eGFR after PCA compared with PN, both approaches result in excellent preservation of renal function.